Improving the ergonomic design of transmission oil cooler hoses: a case study. (1st January 2011) - Awad, Mahmoud; Kovach, Jamison V.
Taguchi methods are often used in industrial applications to redesign existing products or processes within the context of Six Sigma projects. Within the field of product development, ergonomics related issues are becoming increasingly important due to their direct effect on efficiency and productivity. This paper presents a case study within the automotive industry to illustrate how Taguchi methods can be used to redesign transmission oil cooler (TOC) assembly hoses to minimise insertion forces while optimising seal integrity and reduce the potential for leaks. The push-on and pull-off forces for TOC hoses are examined through an experimental study. The results obtained are compared against the original parameter settings to determine the degree of improvement achieved through this study for each design parameter.